Talent Management in Indonesian National Armed Force: Addressing Personnel Bottlenecks - Gati, Rindri Andewi; Utomo, Tri Widodo Wahyu (Puslatbang KDOD Lembaga Administrasi Negara, 2024)
Over the years, the Indonesian National Armed Forces (TNI) has been tasked with upholding state sovereignty and national defence. However, TNI also faces a bottleneck among its middle- and high-ranking officers, leading to excess non-job personnel. Without corresponding promotion adjustments, the current policy will affect the institution's performance and officers' careers. This study applied qualitative research by conducting interviews and gathering primary and secondary data through focused group discussion and literature review from various policy documents and reports. The findings then highlight the solutions with talent management emerging as a strategic approach. It offers a second-best policy option by promoting professionalism and modernity while addressing organisational challenges. Through this approach, we tried to propose evidence-based solutions to improve organisational performance and address personnel bottleneck issues. This study proposes a new approach to talent management strategies. It involves recruiting, developing, and retaining high-potential individuals and optimising functional positions based on expertise to offer an alternative career path. The talent management approach also aims to enhance efficiency and effectiveness within military organisations